Correlation between Psychomotor Skills and Creativity among Secondary School Students and Future Teachers - Honzíková, Jarmila; Krotký, Jan (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The falling level of manual skills of the young generation is one of issues in the 21st century. The existing society asks for creative individuals who can work independently. On the other hand, the manually skilled ones are needed too. The core question of our research was to find out whether the individuals who score high on the test of creativity are at the same time manually skilled. In our opinion, it is important to be creative and manually skilful at once to become successful in these days. To ascertain the relationship between creativity and the level of manual skills, a random sample was selected from children from a secondary school and students of pedagogy. The presented research deals with research regarding levels of creativity and manual skills at secondary schools, that means in the Czech Republic kids from 10 to 14 years old, and at the faculty of education of teachers-to-be. Readers are acquainted with results of evaluating the students of teaching and the pupils/learners at secondary schools from the point of creative abilities in relation with the level of their manual skills. There was used the Urban´s test of creative thinking to test creativity, the level of psychomotor skills was tested using Testing batteries for psychomotor skills, which was made for the research purpose by as. Prof. Honzíková. Those research results as well as the unique testing battery for psychomotor skills are introduced.
Keywords: manual skills; creative abilities; evaluation of manual skills and creativity; teacher training